70.0k views
2 votes
Let f(x) = 2x2 + x − 3 and g(x) = x + 2.

Find (f • g)(x)

2 Answers

2 votes

Answer:

2x^3+5x^2-x-6

Explanation:

f(x) = 2x^2 + x − 3 and g(x) = x + 2.

(f • g)(x) = (2x^2 + x − 3 ) * (x + 2)

Distribute

= (2x^2 + x − 3 )*x + (2x^2 + x − 3 )*2

= 2x^3 +x^2 -3x + 4x^2 +2x -6

Combine like terms

=2x^3+5x^2-x-6

User Sami N
by
6.2k points
3 votes

Answer:


(f\cdot g)(x) = 2x^3 + 5x^2-x-6

Explanation:

We are given the two functions:


f(x)=2x^2+x-3\text{ and } g(x)=x+2

And we want to find:


(f \cdot g)(x)

Recall that this is equivalent to:


=f(x)\cdot g(x)

Substitute. Hence:


(f\cdot g)(x)= (2x^2+x-3)(x+2)

Expand if desired:


\displaystyle = x(2x^2+x-3)+2(2x^2+x-3) \\ \\ = (2x^3+x^2-3x)+(4x^2+2x-6) \\ \\\ = 2x^3 + 5x^2-x-6

User Jagjot
by
6.2k points